Evaluation of Clinical and Genetic Determinants of Treatment OutCome In EGFR Mutation Positive Advanced Lung Adenocarcinoma - Vera Jokic; Katarina Savic-Vujovic; Jelena Spasic; Zoran Bukumiric; Mladen Marinkovic; Davorin Radosavljevic; Milena Cavic (SAGE Publishing, 2022)
Background The aim of this research was to evaluate clinical and low-cost genetic determinants of treatment outcome in EGFR mutation positive advanced lung adenocarcinoma patients. Material and Methods EGFR mutation testing and EGFR 181946C>T genotyping were performed in 101 advanced lung adenocarcinoma patients using qRT-PCR and PCR-RFLP, respectively. Progression-free survival was defined as the time from the start of TKI therapy to date of progression, and overall survival as the time from diagnosis to death from any cause. Pain level was evaluated using a Numerical Rating Scale and the Verbal Descriptor Scale. Statistical significance was considered for P < .05. Results Patients were treated with EGFR-TKIs for a period of 1-39months (median 9), with a median PFS of 12.0 months (10.4-13.6, CI 95%), and a median OS of 19.0 months (15.1-22.7, CI 95%). The presence of pain was significantly correlated with the existence of bone ( P < .001) and adrenal glands metastases ( P = .029). Genetic factors did not have a direct impact on pain management but had a significant effect on the response to TKIs leading to pain alleviation. Conclusions EGFR mutation subtype and the EGFR 181946 C>T SNP had a significant effect on the response to TKI inducing an indirect anti-dolorous effect.